Clinical practice guideline for Sjögren's syndrome 2017. Issue 3 (4th May 2018) - Sumida, Takayuki; Azuma, Naoto; Moriyama, Masafumi; Takahashi, Hiroyuki; Asashima, Hiromitsu; Honda, Fumika; Abe, Saori; Ono, Yuko; Hirota, Tomoya; Hirata, Shintaro; Tanaka, Yoshiya; Shimizu, Toshimasa; et al.
Abstract: Objectives: The objective of this study is to develop clinical practice guideline (CPG) for Sjögren's syndrome (SS) based on recently available clinical and therapeutic evidences. Methods: The CPG committee for SS was organized by the Research Team for Autoimmune Diseases, Research Program for Intractable Disease of the Ministry of Health, Labor and Welfare (MHLW), Japan. The committee completed a systematic review of evidences for several clinical questions and developed CPG for SS 2017 according to the procedure proposed by the Medical Information Network Distribution Service (Minds). The recommendations and their strength were checked by the modified Delphi method. The CPG for SS 2017 has been officially approved by both Japan College of Rheumatology and the Japanese Society for SS. Results: The CPG committee set 38 clinical questions for clinical symptoms, signs, treatment, and management of SS in pediatric, adult and pregnant patients, using the PICO (P: patients, problem, population, I: interventions, C: comparisons, controls, comparators, O: outcomes) format. A summary of evidence, development of recommendation, recommendation, and strength for these 38 clinical questions are presented in the CPG. Conclusion: The CPG for SS 2017 should contribute to improvement and standardization of diagnosis and treatment of SS.